2023
DOI: 10.1002/smll.202207198
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Rapid Substitution of Ti for Zr to Produce Bimetallic (Zr/Ti)UiO‐66‐NH2 with Congenetic “Shell–Core” Structure for Enhancing Photocatalytic Removal of Nitric Oxide

Abstract: Efficient nitric oxide (NO) removal without nitrogen dioxide (NO2) emission is desired for the control of air pollution. Herein, a series of (Zr/Ti)UiO‐66‐NH2 with congenetic shell–core structure, denoted as Ti‐UION, are rapidly synthesized by microwave‐assisted post‐synthetic modification for NO removal. The optimal Ti‐UION (i.e., 2.5Ti‐UION) exhibits the highest activity of 80.74% without NO2 emission with moisture, which is 21.65% greater than that of the UiO‐66‐NH2. The NO removal efficiency of 2.5Ti‐UION … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…5(b), which is determined by the Kubelka-Munk method. 7 This finding is consistent with that in the previous study, 20 and indicates that the prepared UiO-66-NH 2 can respond to low-energy visible light. The existence of photogenerated carriers is confirmed by the photocurrent response plot of the UiO-66-NH 2 sample shown in Fig.…”
Section: Sample Characterizationsupporting
confidence: 92%
See 2 more Smart Citations
“…5(b), which is determined by the Kubelka-Munk method. 7 This finding is consistent with that in the previous study, 20 and indicates that the prepared UiO-66-NH 2 can respond to low-energy visible light. The existence of photogenerated carriers is confirmed by the photocurrent response plot of the UiO-66-NH 2 sample shown in Fig.…”
Section: Sample Characterizationsupporting
confidence: 92%
“…The mass transfer rate at the catalyst surface, j(x) (mol m −2 s −1 ), is calculated using eqn (7). 11,31…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29] Benefiting from the synergistic effects between different components, the charge density and active adsorption sites of the resultant BMOFs will be refreshed. [30,31] MOFs harvest and store water molecules relying on their active adsorption sites and pores, [4,32] so the construction of BMOF offers a novel idea for the design of efficient moisture adsorbents. However, no prior studies have reported the waterharvesting adsorbents based on BMOF and its functionalized forms yet, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…After that, PSM has been increasingly widely used in MOFs. 28–31 Compared to direct solvothermal synthesis, PSM has the advantages of mild reaction conditions, easy control, and can be assembled in multiple steps. For example, Chen et al successfully prepared UiO-66-PDC with the pyridine-2,5-dicarboxylic acid (PDC) ligand by PSM.…”
Section: Introductionmentioning
confidence: 99%